Pengaruh Payment Point Online Bank (PPOB) dalam Percepatan Aliran Kas pada PT PLN (Persero) Distribusi Lampung - Angrita Deziana; Yunus Fiscal; Siti Utami Ningsih (Jurnal Akuntansi dan Keuangan, 2014)
Growth inthe number of customers accompanied by the increasing of electricity bills caused the cash inflow of Â PT PLN (Persero) Distribusi Lampung increased. The conventional systems which were implemented before 2010 need a relatively long time to send cash inflows from customer to the receipt accounts of PT PLN (Persero) Head Office. Therefore, PT PLN (Persero) Distribusi Lampung in 2010 introduced a system of electricity bill payment called Payment Point Online Bank (PPOB). Since the Payment Point Online Bank (PPOB) was applied, and then the cash inflows to the account receipt of PT PLN (Persero) have been faster. The aim of this study was to determine the influence of Payment Point Online Bank (PPOB) in accelerating the cash inflows.The samples in this study were the years of 2009 and 2012 with a36 monthobservation on the average of cash delivery which were received from the customer to the Head Office of PT. PLN (Persero). The type of data used was secondary data and the analytical technique was the Mann-Whitney/Wilcoxon test. The result of analysis using SPSS version 18 shows that there was difference between the Payment Point Online Bank (PPOB) and the conventional systems in accelerating cash inflows with 0.001 < 0.05 of significance value.